THE EFFICACY OF HORMONE THERAPY IN NON-OBSTRUCTIVE AZOOSPERMIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This analysis evaluates the effectiveness of hormone therapy in treating non-obstructive azoospermia. Hormonal interventions, especially in cases of hypogonadotropic hypogonadism, can restore spermatogenesis in 15%–60% of patients, depending on individual factors such as hormone levels, testicular volume, and genetics. While less invasive than surgical methods, success depends on careful patient selection. Advances in personalized and combination therapies offer new potential for improving outcomes.